The materiality key: how work on empirical data can improve analytical models and theoretical frameworks for multimodal discourse analysis - Maiorani, Arianna (Frontiers in Communication, 2024)
This article is a critical reflection on the way the notion of materiality informed the project and the development of The Kinesemiotic Body project carried out by a UK and German research team and of the model of analysis it adopted, the Functional Grammar of Dance. It starts with an excursus of some of the most interesting developments in other discipline that turned to the investigation of materiality as an epistemological perspective, and it shows how the same type of focus has impacted multimodal discourse analysis focusing on movement-based communication. The overarching theme that characterises this multidisciplinary attention to materiality is its anchoring function to the temporal and spatial coordinates in which social phenomena are contextualised, which is taken as the fundamental condition for shaping our perception and understanding of the world in all areas of experience and knowledge. A more specific example of how the notion of materiality impacted the development of movement-based discourse analysis will be provided by an example of analysis of rich movement data captured live from professional dancers from the English National Ballet.